2022
DOI: 10.1111/ceo.14164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of epiretinal membrane: Data from the Korea National Health and Nutrition Examination Survey VII (2017–2018)

Abstract: Background To determine the prevalence and risk factors of epiretinal membrane (ERM) utilising spectral‐domain optical coherence tomography (SD‐OCT). Methods We investigated data from the 2017 to 2018 Korea National Health and Nutrition Examination Survey. Individuals aged ≥40 years with readable fundus photographs and SD‐OCT results were included. ERM was diagnosed by fundus photography and OCT. The following data was collected: demographics, health interview, health examination, and nutritional survey result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Several estimates might explain the correlation between greater IOP fluctuation and ERM. Previous history of cataract surgery is one of risk factors for development of idiopathic ERM [5,32]. In this study, glaucoma patients with ERM showed a higher proportion of eyes with a history of cataract surgery than those without ERM (p = 0.013), even though the correlation did not remain in multiple logistic regression analysis (p = 0.104).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Several estimates might explain the correlation between greater IOP fluctuation and ERM. Previous history of cataract surgery is one of risk factors for development of idiopathic ERM [5,32]. In this study, glaucoma patients with ERM showed a higher proportion of eyes with a history of cataract surgery than those without ERM (p = 0.013), even though the correlation did not remain in multiple logistic regression analysis (p = 0.104).…”
Section: Discussionmentioning
confidence: 53%
“…Old age is one of the well-known factors associated with the presence of ERM [3,4,32]. The correlation between aging and ERM could be related to the findings that PVD develops increasingly with age [32,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ERM prevalence was 7.0% and was positively associated with increasing age, history of cataract surgery, hypertension, and diabetic retinopathy. 2 Data on visual acuity, symptoms, OCT morphology, and intervention for ERM were not available in this study. The authors comment that the prevalence of ERM is lower than those reported in American and European studies, and suggested that variation in ERM prevalence with ethnicity is worthy of further investigation.…”
mentioning
confidence: 95%
“…Kim and colleagues present a robust cross‐sectional study of 6807 randomly selected Koreans from 2017 to 2018, where ERM prevalence was determined with colour fundus photography and high‐definition optical coherence tomography (OCT) 2 . ERM prevalence was 7.0% and was positively associated with increasing age, history of cataract surgery, hypertension, and diabetic retinopathy 2 .…”
mentioning
confidence: 99%